The rare entity of ectopic pancreatic tissue in the gallbladder: A case report. (May 2022) - Chatziantoniou, Georgios; Tzikos, Georgios; Ioannidis, Aristeidis; Loukousia, Antonia; Raptou, Georgia; Michalopoulos, Antonios; Paramythiotis, Daniel
Abstract: Introduction: and importance: Ectopic pancreatic tissue (EPT) is a rare clinical entity, which is defined as the presence of pancreatic tissue without any anatomic or vascular connection with the main body of the pancreas. EPT could be found anywhere in the gastrointestinal tract; most commonly in stomach. The aim of this study is to present a rare case report of EPT located in the gallbladder. Case presentation: A 37-year-old woman was scheduled in our surgical department for elective laparoscopic cholecystectomy due to symptomatic chololithiasis. Preoperative ultrasound imaging was indicative only for the presence of multiple stone tin the gallbladder's fundus. The patient had an uneventful recovery and discharged the first postoperative day. Surprisingly, the final pathology report of the specimen referred the existence of EPT in the subserosa territory, as an incidental finding. Clinical discussion: EPT is almost impossible to be diagnosed preoperatively due to its various clinical presentation and the low discriminating power of all the usual imaging tests. However, given the potential malignant transformation of the EPT, physicians should be aware of this clinical entity and consider cholecystectomy immediately when it is highly suspected. Conclusion: EPT in the gallbladder is a very rare finding. There are no established "gold standard" techniques to identify it preoperatively. The patients are either asymptomatic or presenting with non-specific symptoms and almost always the pathology examination, after cholecystectomy, establishes the definite diagnosis. Highlights: Ectopicpancreatic tissue (EPT) is very uncommon, especially in the gallbladder. Preoperative diagnosis of EPT, although very important due to its potential malignant transformation, is almost impossible. Only awareness of this entity and further research may enlighten more its clinical significance.